Performance of Educational Assessments: Integrated Assessment as an Assessment Innovation during the Covid-19 Pandemic - Eko Handoyo, Ali Masyhar, Kamaludin, Joko Widodo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to find a theoretical concept of assessment for students during the Covid-19 pandemic as a follow-up step for assessment activities in obtaining the validity of assessment results. The research method used is qualitative research methods and conducted on ten Public Elementary School Principals with at least 5 years of teaching experience. The purposive sampling method was used to determine the informants. Here focuses on Analyzing the assessment process and the student learning outcomes process through online learning process during the Covid-19 pandemic. Data collection techniques, in this study, are observation, interviews, and documentation. To obtain data validity, this study uses triangulation of data collection techniques. The result of this study is an integrated assessment theory concept towards the students during the Covid-19 pandemic. The impact of this study provides a new breakthrough, because it provides a different perspective of assessment by integrating 3 perspectives in assessing student academic performance as well as collaborating their own function, namely the teacher's as an assessor of student cognitive competence, the student's as assessors of their own affective competence (self assessment), and the parents’ as assessors of students' psychomotor competencies. The further research can be carried out when the Covid-19 pandemic has ended so that it can provide a different view of the effectiveness of using integrated assessment as an assessment method which can be used sustainably in the future.